Regenerative Medicine Using Pregnancy-Specific Biological Substances - Bhattacharya, Niranjan; Stubblefield, Phillip; SpringerLink (Online service) (London : Springer London, 2011)
Regenerative Medicine Using Pregnancy Specific Biological Substances is an international attempt to bring researchers working on the potential uses of pregnancy specific biological substances in regenerative medicine, under one umbrella. More than 72 distinguished authors from five continents have contributed in the 40 chapters of the book. It will be a good reference source, not only for practicing clinicians, but also for those interested in research in immunotherapy; stem cell therapy; regenerative therapy and various specialities such as cardiology, neurosurgery and cardiothoracic surgery. This book brings together some of the important work that is being done along with unpublished observations that will help to shape the contours of future therapy in the field of modern regenerative medicine. It promises to be an eye-opener to the enormous potential of hitherto discarded material that had been so far considered as a pure biological waste. The book will have served its purpose if it acts as a stimulant to professionals and clinical scientists who can build on the knowledge and expand the curative potential of pregnancy-specific biological substances
Keywords: Medicine; Gene therapy; Internal medicine; Blood transfusion; Hematology; Transplantation of organs, tissues, etc; Medicine & Public Health; Hematology; Blood Transfusion Medicine; Transplant Surgery; Gene Therapy; Internal Medicine